2003
DOI: 10.1093/jnci/djg025
|View full text |Cite
|
Sign up to set email alerts
|

4-Aminobiphenyl-Induced Liver and Urinary Bladder DNA Adduct Formation in Cyp1a2(-/-) and Cyp1a2(+/+) Mice

Abstract: Contrary to our expectations, CYP1A2 expression was not associated with ABP-induced hepatic oxidative stress or with ABP-DNA adduct formation. Either CYP1A2 is not the major metabolic activator of ABP or other enzymes metabolically activate ABP in mice in the absence of CYP1A2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 49 publications
2
58
0
Order By: Relevance
“…In fact, our preliminary study showed that certain dietary isothiocyanates could inhibit the formation of 4-aminobiphenyl-DNA adducts in human bladder cancer cells. 4-Aminobiphenyl, a major carcinogen of human bladder cancer derived from cigarette smoking as well as occupational exposure, causes DNA damage and tumorigenic transformation in the bladder (33)(34)(35)(36), and indeed, 4-aminobiphenyl-DNA adducts were detected in a large percentage of human bladder cancer biopsies and were closely correlated to the amount of cigarettes smoked (37)(38)(39). Thus, it is possible that dietary isothiocyanates derived from cruciferous vegetables may be particularly effective in modifying smoking-related bladder carcinogenesis.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 99%
“…In fact, our preliminary study showed that certain dietary isothiocyanates could inhibit the formation of 4-aminobiphenyl-DNA adducts in human bladder cancer cells. 4-Aminobiphenyl, a major carcinogen of human bladder cancer derived from cigarette smoking as well as occupational exposure, causes DNA damage and tumorigenic transformation in the bladder (33)(34)(35)(36), and indeed, 4-aminobiphenyl-DNA adducts were detected in a large percentage of human bladder cancer biopsies and were closely correlated to the amount of cigarettes smoked (37)(38)(39). Thus, it is possible that dietary isothiocyanates derived from cruciferous vegetables may be particularly effective in modifying smoking-related bladder carcinogenesis.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 99%
“…For example, Cyp1a2 knockout mice do not display lower ABP-DNA adducts (Tsuneoka et al, 2003) nor protection against ABP-induced carcinogenesis (Kimura et al, 1999), despite efficient in vitro N-oxidation of this chemical to a more highly toxic hydroxylamine by Cyp1a2. Similarly, Cyp1a1 knockout mice exhibit increased rather than decreased toxicity from benzo[a]pyrene exposure (Uno et al, 2001(Uno et al, , 2004.…”
Section: Arylamine N-acetyltransferase Nat3(ϫ/ϫ) Knockout Micementioning
confidence: 99%
“…DOI 10.1002/em 2 to generate C8-dG-ABP, which translates into G-T transversions in the genome that can initiate tumor growth by altering the functions of key gene products that control cell survival and proliferation. However, we [Sugamori et al, 2012] and others [Kimura et al, 1999;Tsuneoka et al, 2003] have provided evidence against the involvement of NAT1/2 and CYP1A2 in ABP bioactivation to form C8-dG-ABP, and have also observed no correlation between liver C8-dG-ABP levels and liver tumor incidence. At the same time, a consistent and markedly lower incidence of ABP-induced liver tumors was observed in female mice.…”
Section: Discussionmentioning
confidence: 53%
“…In one widely described bioactivation model based largely on in vitro studies, ABP is first N-hydroxylated by the cytochrome P450 isoform CYP1A2 to a hydroxylamine that is subsequently O-acetylated by arylamine N-acetyltransferase(s) NAT1 and/or NAT2 to form an unstable acetoxy ester [Butler et al, 1989a,b;Hammons et al, 1991;Kadlubar et al, 1991;Kerdar et al, 1993;Hlavica et al, 1997;Guengerich, 2000]. The acetoxy ester spontaneously breaks down to generate a highly reactive nitrenium ion [Novak et al, 1993;McClelland et al, 1995] that can form covalent DNA adducts, which are believed to be critical in the production of mutations that initiate or promote tumor growth Poirier et al, 1995;Otteneder and Lutz, 1999;Tsuneoka et al, 2003]. However, more recent in vivo studies using CYP1A2-deficient Cyp1a2(-/-) mice have provided evidence that is inconsistent with the above model of ABP bioactivation and tumor initiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation